Economic efficiency of animal breeding intensification - Туварчиева, Г. А. («Вісник ЖДТУ»: Економіка, управління та адміністрування, 2005)
Condition of animal breeding development, essence of branch intensification have been considered as well as ways of economic efficiency increasing of animal breeding branch of agriculture have been determined.